Consumers’ Responses to Corporate Social Responsibility Initiatives: The Mediating Role of Consumer–Company Identification - Deng, Xinming (Journal of business ethics, 2017)
In order to explore the mechanism of consumer responses to corporate social responsibility (CSR), this paper constructs a research framework including CSR, consumer–company identification (CCI), consumer responses, and fit, and tests the framework using a scene-questionnaire survey. Empirical results demonstrate that CSR not only has positive influence on consumer purchase intention, recommend intention, and loyalty directly, but also has indirect positive influence on consumer purchase intention and recommend intention through CCI. The influencing process of CSR on CCI is moderated by fit and the moderating direction is different owing to product types. For the products whose association preference is positive, fit can positively moderate the relationship between CSR and CCI, while for products whose association preference is negative, the moderating role will be negative.